Volume 2: 34th Annual Mechanisms and Robotics Conference, Parts a and B 2010
DOI: 10.1115/detc2010-28978
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic-, Static- and Workspace Analysis of a 6-P-U-S Parallel Manipulator

Abstract: This paper examines the symbolic kinematic modeling of a general 6-P-U-S (prismatic-universal-spherical) parallel kinematic manipulator (PKM). The base location of actuators has been previously shown to lead to: (i) reduction of the (motor) weight carried by the legs; (ii) elimination of the actuation transmission requirement (through intermediary joints as in the case of the Stewart-Gough platform); and (iii) most-importantly absorption of reaction-forces by the ground. We focus on using the symbolic equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…However, our primary interest is to apply this workspace optimization framework to enhance the workspace of a 6-P-U-S parallel manipulator, whose kinematic study was reported in [11][12]. This parallel manipulator consists of six legs, each having a P-U-S architecture as shown in Figure 2 and Figure 3.…”
Section: B 6-p-u-s Parallel Manipulatormentioning
confidence: 99%
“…However, our primary interest is to apply this workspace optimization framework to enhance the workspace of a 6-P-U-S parallel manipulator, whose kinematic study was reported in [11][12]. This parallel manipulator consists of six legs, each having a P-U-S architecture as shown in Figure 2 and Figure 3.…”
Section: B 6-p-u-s Parallel Manipulatormentioning
confidence: 99%
“…This development is examined specifically in the context of deriving controlled force-displacement data from a standard biopsy phantom (called Blue Phantom T M , refer Fig.1(a)). The experiments were conducted using a 6 DOF testing machine [10] that is attached with a 6 DOF force transducer. Development of such a haptic model could then facilitate testing of trainees with either the (i) real phantom (or) (ii) virtual phantom interchangeably using our simulator framework.…”
Section: Dscc2012-movic2012-8658mentioning
confidence: 99%
“…The material characteristics of the BluePhantom T M were determined by performing a series of needle insertion experiments. For this purpose, a 6-DOF robotic platform as in [10], equipped with a 6 DOF force-torque transducer (ATI Delta) is used that served as an effective material testing system (MTS) as shown in Fig.5. The resolution of the force transducer as well as platform translation is summarized in this graph and found to be suitable for our application.…”
Section: Experimental Testbedmentioning
confidence: 99%
“…One advantage that this model (6-PUS) has over the traditional 6-UPS is that the actuators remain fixed on the base. In some cases, this simplifies the construction of the robot and, on the other hand, causes part of the payload to be supported by the reaction forces of the floor [9]. Thus, the actuators require less load capacity.…”
Section: Introductionmentioning
confidence: 97%